ANALISIS ANGKA KEJADIAN READMISSION KASUS SKIZOFRENIA - HARJANTI -; Lieska Wulandari (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Based on a preliminary survey in RSJD dr. Arif Zainudin Surakarta, schizophrenia is one of top 10 diseases and the number of its readmission in 2015 as much as 1296 patients. This type of this research is descriptive research with retrospective approach. The writer did this research in dr. Arif Zainudin Regional Mental Hospital Surakarta on November until December 2017. The populations of this research are all patients of schizophrenia readmission. Subyek of the medical recorderof the analising reporting and the object used is the monthly report book hospitalized. The writer uses observation and unstructured interview to collect the data. The dwarfs used are processing collecting, editing, presentation of data, and descriptive analysis as the data analysis. The results of this research is the number of schizophrenia patients are 2046 patients, 56% or 1136 patients are schizophrenia readmission. Based on the sex of the patient, male is more frequently experienced of readmission, it is 71%. Based on the age of the patient, it is most occur in the young adult age, it is 37%, and based on the types of schizophrenia, the most is schizophrenia unspecified, it is 47%. One of the schizophrenia readmission factors is the role of themselves and their family in the healing process. The conclusion of this research is; the highest readmission case is schizophrenia. It is recommended to increase the socialization to the patient and their family about the treatment of the patient. For quality improvement, medical officers may also provide the additional control schedules to the special patients (based on time of back, sex, age, and type of schizophrenia), so it can prevent the readmission